The grammatical term for Al-Samin Al-Halabi in his book Follow Favorit (Journal of the College of Basic Education, 2023)
In order to shed light on Al-Sameen’s grammatical doctrine, we preferred to show the terms he used in his book Al-Durr Al-Masun, whether they are Kufic or Basra, and there was a great disagreement between the Kufans and the Basrans in the field of the grammatical term until it became common among later scholars that this term is visual and that term is Kufic ().The contemplator in the book Al-Durr Al-Masun and the follower of Al-Samin Al-Halabi’s opinions and his choices in it, sees that he was the visual of the doctrine, and if he did not declare that, the majority of grammarians agreed with their visuals and coffins in most of what he went to, and rarely disagreed with them, and the visualization of Al-Samin becomes more clear through the grammatical terms that he used in his book . However, he did not overlook the Kufic terminology that was mentioned in his book, on the grounds that it does not reach the degree of its predecessor, and this may be because the Kufic term was not written for it as common as the visual term, and a clear and complete picture of it did not reach us, and this may be due to the loss of most of the books of the owners of this doctrine Likewise, most of what has come down to us from their writings does not fall into the section of grammar, but falls into other sciences such as language and interpretation (), such as the books of Al-Farra’, Ibn Al-Sakit, Tha’lab, and Abu Bakr bin Al-Anbari.We will now present a set of terms that we have extracted from the book Durr Al-Masun by Al-Sameen Al-Halabi.